PREVALENCE AND DETERMINANTS OF PROTEIN-ENERGY MALNUTRITION (PEM) AMONG CHILDREN UNDER 5 YEARS OF AGE IN A RURAL COMMUNITY OF LAHORE - RASHEED , A; FIRDOS , U; SEEMAB , F; RANI , M; HANIF , K; HANIF , S; SIDDIQUE , S; ZAFAR , M (Biological and Clinical Sciences Research Journal, 2023)
Malnutrition refers to an inadequate supply of nutrients and energy to the body cells, compared to the body's requirements for maintaining growth and ensuring daily functions. It is a major health burden in developing countries and can be categorized as under-nutrition and over-nutrition. This study aimed to determine the prevalence and determinants of Protein Energy Malnutrition (PEM) among children under 5 years of age in a rural community of Lahore. A quantitative descriptive cross-sectional study was conducted in the Lakhodair community of Lahore. A sample of 150 married females participated in the study, and a purposive sampling was used to collect data. The results revealed that 43% of the participants were male mothers, and 57% were female. PEM was categorized as mild, moderate, and severe. Severe PEM was noted in children under the age of 5 years in this Lakhodair community, with an incidence rate of 4.22%. It was concluded that the prevalence rate of PEM among children under 5 years of age in a rural community of Lahore was 4.22%. Protein Energy Malnutrition (PEM) determinants include protein and carbohydrate intake, housing and environmental status, father and mother's education and occupation, monthly income, socio-economic factors, dietary habits, family size, and anthropometric measures.